Mapping Quranic Exegesis Research: Trends, Contributions, and Future Directions - Andri Nirwana AN; Yeti Dahliana; Ainur Rhain; Kharis Nugroho; Ahmad Nurrahim; Alfiyatul Azizah; Zainora Daud (SCAD Independent, 2025)
Indexed by WOS/Scopus/ERA